Implementation of single minute exchange die (SMED) technique to accelerate the mold changing time at sme company - Muhamad Nasruldin, Hashim (2012)
The purpose of the Single Minute Exchange Die (SMED) is to eliminate waste of time. Longer set-up time means that the production line is not productive and will left behind by their competitor. Nowadays, everything is been done faster and just-in-time, where manufactures need to produced product in fast and without neglecting the quality issue and deliver it to customer right on time. In this project, SMED had provided the method to eliminate waste of time with their eight technique of SMED introduced by Mr. Shigeo Shingo. In SMED mold or die exchange should be less in 10minute and it took lots of improvement involve by the employee. The project objective is to reduce mold set-up time to 40% is exceeding the expectation where they able to reduce until 51% from the total setup time previously. In overall with the help of everyone, especially from top management of company to their employee, SMED is successfully done and achieve the objective.